2017
DOI: 10.1371/journal.pone.0170305
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Human Anti-Platelet scFv Antibody Produced in Pichia pastoris for Atheroma Targeting

Abstract: Cells of the innate and adaptive immune system are key factors in the progression of atherosclerotic plaque, leading to plaque instability and rupture, potentially resulting in acute atherothrombotic events such as coronary artery disease, cerebrovascular disease and peripheral arterial disease. Here, we describe the cloning, expression, purification, and immunoreactivity assessment of a recombinant single-chain variable fragment (scFv) derived from a human anti-αIIbβ3 antibody (HuAb) selected to target athero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…11 Here we used a smaller format, TEG4 2c scFv, engineered to harbor terminal cysteines which allowed for oriented and site specific grafting to the terminal maleimide functions borne by VUSPIO nanoparticles. 19 Surface plasmon resonance experiments showed that this newly engineered format was able to bind to its target, the purified integrin αIIbβ3, both unconjugated and after conjugation to nanoparticles, justifying the interest of this oriented grafting. It was further proven by immunofluorescence experiments that this format maintained its reactivity to atheroma lesions as it was shown to label the same structures as a commercial anti CD41 antibody (see Supporting Information), both before and after conjugation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…11 Here we used a smaller format, TEG4 2c scFv, engineered to harbor terminal cysteines which allowed for oriented and site specific grafting to the terminal maleimide functions borne by VUSPIO nanoparticles. 19 Surface plasmon resonance experiments showed that this newly engineered format was able to bind to its target, the purified integrin αIIbβ3, both unconjugated and after conjugation to nanoparticles, justifying the interest of this oriented grafting. It was further proven by immunofluorescence experiments that this format maintained its reactivity to atheroma lesions as it was shown to label the same structures as a commercial anti CD41 antibody (see Supporting Information), both before and after conjugation.…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, to better control the antibody to probe conjugation ratio and the fragment orientation, this scFv was engineered to present two terminal cysteines that allowed for site directed grafting to maleimide residues on the surface of the nanoparticle. 19 Indeed, usual conjugation strategies involve the reaction of amine side chains of the antibodies, which may be a good strategy for full IgG but presents the risk to degrade the binding sites of smaller antibody fragments and impede their reactivity. Avidity and reactivity of the functionalized nano object were assessed in vitro by surface plasmon resonance (SPR) on purified integrin αIIbβ3 and immunohistochemistry (IHC) on fixed atheromatous tissue, and confirmed the expected benefit of multifunctionalization.…”
mentioning
confidence: 99%
“…Considering that various His-tag-fused cytokines and growth factors with normal functions can be prepared readily, our method could be widely applicable to many combinations of cytokines and growth factors. Also, given that a few His tag tethered antibodies (including scFv) have been reported to bind an epitope of the target receptor without loss of function on living cells, [46][47][48] we envision that our technique with His-tagged antibodies enables a variety of endogenous receptor labeling on living cells.…”
Section: Resultsmentioning
confidence: 99%
“…TEG4 recombinant scFv was further processed in Pichia pastoris, which is an attractive system for a cost-effective, large-scale production of heterologous proteins. 154 This type of production, which is characterized by the secretion of the protein of interest into the culture medium, can be easily scaled up and reach a GRAS (generally recognized as safe) status. The scFvs activated with the TCEP (tris(2-carboxyethyl)phosphine) reagent were conjugated to the surface maleimides of the bimodal VUSPIO.…”
Section: Integrin αIibβ3mentioning
confidence: 99%